Exploring Pronunciation Problems Faced by Undergraduate Students - Yulianawati, Ida (Journal of English Development, 2025)
Pronunciation is a critical component of language proficiency, yet many undergraduate students face persistent challenges in achieving intelligible pronunciation. This study explores the pronunciation difficulties encountered by undergraduate students, identifying key problematic phonemes, suprasegmental features, and underlying factors contributing to these challenges. A qualitative approach was employed, utilizing interviews, observations, and pronunciation tests to collect data from undergraduate students in an English language program. Findings reveal that difficulties primarily stem from first-language interference, limited phonetic awareness, and insufficient exposure to native-like pronunciation models. Moreover, suprasegmental features such as intonation and stress patterns significantly impact intelligibility. The study underscores the need for pedagogical interventions, including explicit pronunciation instruction and technology-enhanced learning strategies, to address these issues effectively. The findings contribute to the growing body of research on pronunciation challenges and offer insights for educators seeking to enhance students’ spoken English proficiency.